Case reportTransient cortical blindness after coronary artery angiography - Terlecki, Michał; Wojciechowska, Wiktoria; Rajzer, Marek; Jurczyszyn, Artur; Bazan-Socha, Stanisława; Bryniarski, Leszek; Czarnecka, Danuta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Coronary angiography is the current gold standard for the diagnosis of ischemic heart disease and therefore the prevalence of percutaneous coronary procedures such as angiography and angioplasty is high. The occurrence of cerebral complications after coronary angiography and coronary angioplasty is low and it mainly includes transient ischemic attack and stroke. The prevalence of transient cortical blindness after X-ray contrast media is low and it is usually seen after cerebral angiography. Until now only a few cases of transient cortical blindness have been described after coronary artery angiography. Regarding the spread of coronary angiography worldwide and in Poland this complication is uniquely rare. A 32-year-old man with multiple extrasystolic ventricular arrhythmia suggesting Brugada syndrome diagnosis according to morphology of the left bundle branch block and with decreased left ventricular ejection fraction was admitted to the First Department of Cardiology and Hypertension, Medical College of the Jagiellonian University in Krakow. Coronary angiography was performed in order to exclude ischemic etiology of the observed abnormalities. No arteriosclerotic lesions were found in coronary arteries. Transient cortical blindness was observed directly after angiography which may have been caused by the neurotoxic effect of the used X-ray contrast medium. In ophthalmologic and neurologic examination as well as in the cerebral computed tomography scan no pathologies were found. Visual impairment disappeared totally within several hours.